Broadband Matching of Patch-Antenna for Geolocation - M. A. Yantsevich; G. A. Filipovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article presents the study results of the possibilities of expanding the working frequency band of a patch antenna, due to the broadband matching. As a systematic approach, a generalized Darlington method is proposed using flexible approximating functions with increased variable properties. These properties are necessary for the solvability of the system of restrictions on the agreement limits. The results of synthesis by the generalized Darlington method using flexible approximations provide a matching band of 10 %, but have an increased sensitivity of the values of concentrated elements. A synthesis technique in a distributed element basis is also presented. In the synthesis of a matching chain on distributed elements, the Richards transform for homogeneous microstrip lines is used. A comparison of theoretical and experimental results of antenna matching is presented. Synthesis on distributed elements provided a 17 % band with a minimum number of matching elements. The synthesis technique in the distributed element basis can be used to match a wide class of vibrator and slot antennas, the dimensions of which are multiples of a wavelength quarter.